Possible methods and approaches for verification of undeclared and decommissioned sites for verifying nuclear disarmament, the reasons to employ them, and the dissemination of findings - Várdai Mihail I. (2021)
The future verification of the nuclear disarmament poses different challenges. The International Partnership for Nuclear Disarmament Verification is working on these challenges. The verification methods and approaches are very different so they can greatly influence the outcome of the inspection activities.